2021
DOI: 10.1002/adtp.202000278
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Fluorophores for Thrombosis Diagnosis and Therapy

Abstract: Thrombosis is an adverse physiological event wherein the resulting thrombus and thrombus‐induced diseases collectively result in high morbidity and mortality rates. Currently, nano‐medicines that incorporate fluorophores emitting in the near‐infrared‐I (NIR‐I, 700–900 nm) spectral region have been adopted to afford thrombosis theranostics. However, several unsolved problems such as limited penetration depth and image quality severely impede further applications of such nano‐medicine systems. Fortunately, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In addition to cardiovascular system, the peripheral vascular system includes blood vessel network of limbs (arms and legs) as well as other remote regions of the body, away from the heart and major organs. ,,, Comprising arteries, veins, and capillaries, the intricate system facilitates the circulation of oxygenated and deoxygenated blood between peripheral tissues and organs . The provision of accurate and timely feedback on vascular information plays a pivotal role in effective management of peripheral vascular diseases. , Examples of common peripheral vascular diseases encompass atherosclerotic occlusion, arteriovenous thrombosis, peripheral artery disease, varicose veins, deep vein thrombosis, and peripheral venous disease. , Fluorescence imaging in the NIR region has emerged as an exceptional technique for visualizing intricate details of the peripheral vasculature, offering high spatial resolution and an enhanced SNR. , Jiang et al developed a cosensitization strategy to adjust the photonic properties of lanthanide-doped nanocrystals, enabling both upconversion and downconversion luminescence while possessing ultrawideband absorption (Figure ). The cosensitized lanthanide-doped nanocrystals were designed using Ho 3+ and Nd 3+ as cosensitizers, Yb 3+ as the mediator, and Er 3+ (or Ho 3+ , Pr 3+ , and Tm 3+ ) as the activators.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…In addition to cardiovascular system, the peripheral vascular system includes blood vessel network of limbs (arms and legs) as well as other remote regions of the body, away from the heart and major organs. ,,, Comprising arteries, veins, and capillaries, the intricate system facilitates the circulation of oxygenated and deoxygenated blood between peripheral tissues and organs . The provision of accurate and timely feedback on vascular information plays a pivotal role in effective management of peripheral vascular diseases. , Examples of common peripheral vascular diseases encompass atherosclerotic occlusion, arteriovenous thrombosis, peripheral artery disease, varicose veins, deep vein thrombosis, and peripheral venous disease. , Fluorescence imaging in the NIR region has emerged as an exceptional technique for visualizing intricate details of the peripheral vasculature, offering high spatial resolution and an enhanced SNR. , Jiang et al developed a cosensitization strategy to adjust the photonic properties of lanthanide-doped nanocrystals, enabling both upconversion and downconversion luminescence while possessing ultrawideband absorption (Figure ). The cosensitized lanthanide-doped nanocrystals were designed using Ho 3+ and Nd 3+ as cosensitizers, Yb 3+ as the mediator, and Er 3+ (or Ho 3+ , Pr 3+ , and Tm 3+ ) as the activators.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…Accordingly, both thrombolytic medicines and contrast agents should be placed onto one single-drug carrier. However, there tends to be a paucity of publications that utilized NIR-II dyes for the diagnosis of thrombotic disease [ 36 ]. One concern with NIR-II dyes is their extreme hydrophobicity and insolubility in water [ 37 ], which impedes their efficient encapsulation into drug carriers for targeted delivery to thrombotic lesion sites.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is the most common form of endocrine malignancy that has seen a significant rise in incidence rates in recent decades. Some studies have reported an elevation in the expression of DPP-IVa biomarker for malignancy in thyroid nodules and thyroid cancers. Imaging remains the most effective diagnostic method for significant human lesions; thus, we have developed a new method for the diagnosis of thyroid nodular lesions, which challenges conventional imaging or needle biopsy. , Typically, confirming a diagnosis requires several days of extensive pathological examination, and the process is laborious and heavily reliant on the pathologist’s subjective judgment . In recent years, near-infrared (NIR) fluorescent probes have been proven particularly valuable in identifying and imaging biomolecules owing to their high tissue penetration and the ability to bypass autofluorescence; thus, they have become the tools widely used in disease diagnosis and treatment. …”
Section: Introductionmentioning
confidence: 99%